Effects of copper, iron and zinc in the ration on the performance of growing-finishing pigs - Bellaver, Claúdio; Gomes, Paulo Cezar; Sobestiansky, Jurij; Fialho, Elias Tadeu; Brito, M. A.V.P.; Freitas, Alfredo Ribeiro de; Protas, José Fernando (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted to test copper, iron and zinc levels in pig diets formulated based on corn, soybean meal, minerals and vitamins. Feeds over gain ratio (Y) in the total experimental period was similar (P>0.05) for 125 and 250 ppm levels of copper (X) both differing from the level of 6 ppm. The linear effect (Y = 3.3165 - 0.0005325X) was significant with R2 = 0.78. The variance analysis for average daily gain did not show significative effects (P>0.05), but the regression analysis showed that the levels of copper (X) did influence on average daily gain (Y) according to the equation: Y = 555.06 + 0.42475X - 0.00178X2 with R2 = 0.99. The levels of 6, 125 and 250 ppm of copper in the ration showed a linear increase of copper storage in the liver, being respectively 74, 432 and 1306 ppm based on the dry matter. This increase of copper in the liver was responsible for a decrease of iron and an increase of zinc in the liver when the ration was treated with 250 ppm of copper. This iron decrease caused a microcitic hipocromic anemia, which explains the lower performance of the animals consuming diets with 250 ppm of copper. Based on the results and economicanalysis it was concluded that the level of 125 ppm of copper in the ration was responsible for a better performance of the animals without any risc of toxicity to them or even to man.
Keywords: minerals; microelements; hematology; carcass; growth promotor; additive; antimicrobiologicals